2000
DOI: 10.1001/archinte.160.3.349
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-Converting Enzyme Inhibitors, Calcium Channel Blockers, and Breast Cancer

Abstract: The findings of this large case-control analysis do not support the hypothesis that longer-term use of ACE inhibitors or CCBs affects the risk of developing breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
82
2

Year Published

2001
2001
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(86 citation statements)
references
References 21 publications
2
82
2
Order By: Relevance
“…In a previous study our group found that diagnoses of cancer are validated in 95% of cases for whom further information is obtained from general practitioners (Jick et al, 1997). Thirty of 30 randomly selected probable cases of breast cancer were confirmed in an earlier review of their pathology report or hospital discharge summary (Meier et al, 2000). Also, we recently reported that the age-adjusted incidence rates of breast cancer among women in the GPRD are closely similar to those reported by the UK Office of National Statistics (Kaye et al, 2000).…”
mentioning
confidence: 59%
“…In a previous study our group found that diagnoses of cancer are validated in 95% of cases for whom further information is obtained from general practitioners (Jick et al, 1997). Thirty of 30 randomly selected probable cases of breast cancer were confirmed in an earlier review of their pathology report or hospital discharge summary (Meier et al, 2000). Also, we recently reported that the age-adjusted incidence rates of breast cancer among women in the GPRD are closely similar to those reported by the UK Office of National Statistics (Kaye et al, 2000).…”
mentioning
confidence: 59%
“…The risk estimate for diltiazem use was correspondingly increased, but nonsignificant [4,5,9,13]. On the other hand, five case-control studies [10,11,13,15,20] and several cohort studies [9,12,14,[21][22][23][24] and an analysis of verapamil use within a randomised controlled trial [25] suggested no association between CCBs and cancer. However, a major limitation of most of these studies is the exposure assessment at baseline without detailed information on continuous drug use [5,6,[8][9][10][11][12]14,[21][22][23].…”
Section: Antihypertensivesmentioning
confidence: 99%
“…This may have led to a misclassification of exposure. In addition, confounder adjustment was found to be insufficient in most of studies mentioned [8,22,24], also due to the limitations of registrations [9,15]. Continuous exposure to CCB with a drug prescription history of several years and detailed use pattern is needed to investigate the association with cancer and is provided in only a few studies [13,15,24].…”
Section: Antihypertensivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparison with a matched control group of 14 155 women did not support the hypothesis that use of ACE inhibitors affects the risk of malignancy. 54 Stahl et al 55 Likewise, in the population-based Prescription Database of North Jutland County and the Danish Cancer Registry, cancer incidence among 17 897 individuals prescribed ACEis did not confirm a protective effect of ACEi on the development of cancer. 56 In the Swedish trial STOP-Hypertension-2, comprising 6614 hypertensives, there were 625 new cases of cancer in 590 patients.…”
Section: Clinical Observationsmentioning
confidence: 96%